Pendampingan Penyusunan Laporan Keuangan UMKM Dan Optimalisasi Potensi Desa Panggoi, Muara Dua, Lhokseumawe - Indrayani Indrayani; Murhaban Murhaban; Nurhasanah Nurhasanah; Hanif Hanif; Zainal Abidin (Asosiasi Dosen Akuntansi Indonesia, 2022)
Community service is carried out in the Meunasah Panggoi Village, which is located in Muara Dua District, Lhokseumawe City. The purpose of holding this service activity is to (1) increase population awareness of the importance of financial recording of MSME activities in the context of better decision making (2) Improve the quality and competence of village youth as the next generation who will develop and advance the village (3) optimize village potential (4) assisting village officials in the process of compiling accounting journals related to the APBDesa realization report. To achieve this goal, community service has been carried out from June to November 2021, namely the holding of a series of training activities for the preparation of simple financial reports for MSMEs, as well as English language training. Meanwhile, to achieve goals number 3 and 4 above, the service team in this year's activity has only collected data related to village potential and village funds and proposed a number of things to optimize both of them.